Modelling and Control of a Small Domestic Wind Turbine - Cherif, Hakima; Khechekhouche, Abderrahmane; Maamir, Madiha; Aboub, Hania; Belgasim, Basim (Universitas Pendidikan Indonesia (UPI), 2023)
A wind turbine is a machine that converts the kinetic energy of wind into mechanical energy like wind turbines. This mechanical wind power has been used through the ages to pump water or grind grain. Current machines are used to produce wind-type electricity which is consumed locally (isolated sites), or injected into the electricity network (wind turbines connected to the network). In this work, we are only interested in the modelling of a three-bladed horizontal axis wind turbine. All the models were developed by the Matlab/Simulink software, which makes it possible to set up fairly quickly models as well as the associated. The results revealed that the wind profile ranges between 6-7 (m/s), the power coefficient Cp for a pitch angle of =2 has an average value of 0.54 with a relative speed λ value of 6.40, and when the origin of electrical losses is ignored, the electrical power equals the electromagnetic power, and the mechanical speed is stable between (70-80 rd/s).